Migrant labour market integration: the association between initial settlement and subsequent employment and income among migrants. Issue 2 (3rd April 2019) - Wimark, Thomas; Haandrikman, Karen; Nielsen, Michael Meinild
ABSTRACT: The neighbourhood effects literature indicates that a person's place of residence may affect their socio-economic situation. This study examines the association between the initial settlement and immigrants' employment and income. Previous studies mostly used administratively defined geographical units of study, which may have led to an underestimation of neighbourhood effects. The current study uses individualized neighbourhoods, where neighbourhoods are constructed based on each individual's closest neighbours using geocoded register data, on different scales. In this way, more of the individual's actual neighbourhood is captured. The longitudinal study follows three cohorts of migrants and examines the relationship between the initial neighbourhoods that migrants settle in and their employment and income, in the short and medium-long term. The results show clear associations between neighbourhoods of initial settlement and labour market integration. Starting off in neighbourhoods with high levels of deprivation is associated with lower levels of employment while settling in affluent neighbourhoods is associated with higher incomes. Findings are stable for different migrant cohorts and in the short and long term. Neighbourhood effects are substantial especially for those settling in the most deprived or the most affluent neighbourhoods.